2021
DOI: 10.1186/s13047-020-00435-7
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical guidance for podiatrists in the management of foot problems in rheumatic disorders: evaluation of an educational programme for podiatrists using a mixed methods design

Abstract: Background Foot and ankle problems are common in rheumatic disorders and often lead to pain and limitations in functioning, affecting quality of life. There appears to be large variability in the management of foot problems in rheumatic disorders across podiatrists. To increase uniformity and quality of podiatry care for rheumatoid arthritis (RA), osteoarthritis (OA), spondyloarthritis (SpA), and gout a clinical protocol has been developed. Research objectives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…We were not able to find the registered number of podiatrists working in Saudi Arabia. A research study from the Netherlands found that podiatrists perceived that there was an improvement in patient management after they had participated in an educational training program [37].…”
Section: Discussionmentioning
confidence: 99%
“…We were not able to find the registered number of podiatrists working in Saudi Arabia. A research study from the Netherlands found that podiatrists perceived that there was an improvement in patient management after they had participated in an educational training program [37].…”
Section: Discussionmentioning
confidence: 99%
“…Results from this study have also demonstrated the range of foot-care interventions provided to people with inflammatory rheumatic diseases. Consistent with current guidelines and expert recommendations [14,[24][25][26][27][28], patients attending the AUT Podiatric Rheumatology Clinic received treatment of skin and nail problems, wound care, clinical padding, foot orthoses, and footwear prescription and advice. However, the most common intervention was foot-care education, provided during almost all appointments.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, in reference to wait times, the relatively short wait times between referral and appointment observed in the current review are promising (median ~2 months). The majority of patients also attended regular four-monthly appointments which may support the importance of regular foot-care to prevent the development of new foot problems and address the changing concerns of the patient over time [14,[24][25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…Following publication of the original article [1], we were notified that Fig. 2 should be the figure of the supplementary material (Additional file 2).…”
mentioning
confidence: 99%